Macular Thinning and Microvasculature Abnormalities in Children with Sickle Cell Disease: A Longitudinal Analysis - Sally S. Ong, MD; Ann Nampomba, MS; Sara Rahman, BS; Loka Thangamathesvaran, MD; Grace Reilly, MD; Jianqiao Ma, ScM; Jay Vaidya, PhD; Sophie Lanzkron, MD, MHS; Adrienne W. Scott, MD (Ophthalmology Science)
Purpose: To assess longitudinal changes in retinal thickness and vessel density (VD) in pediatric sickle cell disease (SCD). Design: A prospective cohort study. Participants: Children (<18 years old) with HbSS and HbS variant (HbSC and HbS thalassemia) genotypes were enrolled from a university-based retina subspecialty clinic from 2017 to 2019 and followed for ≥2 years. Methods: Participants received 3 × 3 and 6 × 6 mm OCT and OCT angiography scans at baseline and at each follow-up visit. Main Outcome Measures: Retinal thickness, superficial capillary plexus (SCP), and deep capillary plexus (DCP) VD were compared over time. Results: Children with HbSS (n = 14) and HbS variant (n = 14) genotypes with ≥1 follow-up were included in the study (total 56 eyes). For HbSS, rates of retinal thinning per year were significant in the inner retina in the nasal, inferior, and total parafovea (P = 0.002, 0.003, and 0.03 respectively), temporal and total perifovea (P = 0.01 and 0.02); in the middle retina in the superior perifovea (P = 0.04); and in the total retina in the superior, nasal, and total perifovea (P < 0.001, = 0.01, and 0.009). For HbS variant, the rate of retinal thinning was significant in the inner retina in the superior parafovea (P = 0.002) only. Vessel density did not change in the SCP in HbSS subjects in any of the subfields studied but increased significantly in the SCP in HbS variant subjects in the nasal and inferior parafovea (P = 0.02 and 0.045) and superior and nasal perifovea (P = 0.03 and 0.004). Vessel density in the DCP increased in the HbSS group in all the subfields studied (P < 0.05) and in the HbS variant group in the temporal parafovea (P = 0.02). Conclusions: Progressive retinal thinning, predominantly in the inner retinal layers, was particularly notable in children with HbSS disease. This was observed in conjunction with the lack of an increase in the SCP VD in the HbSS group when compared with the HbS variant group. These findings suggest that microstructural and microvasculature abnormalities in the macula start in childhood in SCD, especially for those with HbSS disease. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.